PRODUKSI PUPUK ORGANIK CAIR (POC) DARI SAMPAH ORGANIK RUMAH TANGGA DAN PASAR MELALUI TEKNOLOGI AQUA+ DAN NANO FIT DI DESA HANURA, PESAWARAN - Syaiful Bahri; Sutopo Hadi; Fiqri Fauzan Hadi; Nabila Putri Ananda; Yuli Ambarwati; Notiragayu Notiragayu; Lina Marlina; Ganjar Andhulangi (Universitas Mataram, 2026)
The limited availability of subsidized fertilizers has become a major challenge for farmers in Hanura Village, Teluk Pandan District, Pesawaran Regency, Lampung, Indonesia, as identified through discussions with local authorities. This issue has led to a decline in agricultural productivity. Liquid Organic Fertilizer (LOF) produced from household and market organic waste offers a sustainable alternative. However, the community’s perception of the complex LOF production process remains an obstacle to broader adoption. To address this challenge, this program aimed to educate and implement a bioenergy-based LOF production process from organic waste using Aqua+ and Nano Fit technology in the village. The community service program applied appropriate technology, including shredders and pressing machines, to process organic waste into LOF. The Aqua+ and Nano Fit system enhanced nutrient extraction efficiency and simplified the production process for community use. The program successfully developed and operated one unit of Aqua+ and Nano Fit equipment capable of converting organic waste into liquid fertilizer and solid residue. Approximately four liters of Aqua+ and Nano Fit-based POC were produced, characterized by stable pH, neutral odor, and suitability for agricultural application. The training, attended by 20 participants, improved community understanding and interest in independent waste processing, increasing the average knowledge score from 37.1% to 82.2%. Moreover, initial support from the Village-Owned Enterprise or BUMDes was secured to ensure program sustainability. In conclusion, this community service program effectively implemented POC production using Aqua+ and Nano Fit technology, enhancing community awareness and promoting sustainable organic waste management practices in Hanura Village.